Distinguishing Forest Tree Communities In Kibale National Park, Western Uganda Using Ordination And Classification Methods - Mucunguzi, Patrick; Kasenene, John; Midgley, Jeremy; Ssegawa, Paul; Tabuti, John R. S. (African Journal of Ecology, 2007)
A study of spatial variation in tree community structure and species composition in the Kibale National Park, western Uganda was conducted. Tree communities were compared at five sites namely K-14, K-15 and K-30 at Kanyawara in the north, Ngogo in the central part of the forest and Mainaro in the southern part. All trees ≥10-cm diameter at breast height were censused along belt transects covering a total of 15 ha in all sites. Cluster analysis and principal component analysis were used to identify forest tree communities and species associations. Using cluster analysis, two species assemblages emerged: the Mainaro, Ngogo and K-15 cluster and the K-30 and K-14 cluster. Principal component analysis revealed the descriptive species for the northern and southern sites.
Keywords: ordination, species associations, tree community